2023
DOI: 10.1029/2023gl105389
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Aerosols Contribute to the Recent Decline in Precipitation Over the U.S. Southwest

Yan‐Ning Kuo,
Hanjun Kim,
Flavio Lehner

Abstract: The winter‐spring precipitation over the Southwestern United States (SWUS) decreased since 1980. It is frequently attributed to Pacific internal decadal variability, but recent studies found anthropogenic aerosols (AA) can also induce a transition to a negative Pacific Decadal Variability (PDV) phase. We revisit the attribution of SWUS drying by quantifying the contributions of anthropogenically forced decadal Pacific Sea Surface Temperatures (SSTs). Applying a low‐frequency component analysis to observations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
0
0
0
Order By: Relevance
“…While AO-GCMs predicted a warming SST trend in the Central and East Pacific, the region instead experienced a cooling SST trend from 1970 to 2014 (e.g., Coats & Karnauskas, 2017;Seager et al, 2019), which potentially led to the observed megadrought in the SWUS due to a decrease in precipitation (Delworth et al, 2015;Seager & Hoerling, 2014). The cooling of the Central and East Pacific not simulated by AO-GCMs may have been caused by a forced response to greenhouse gas emissions (Coats & Karnauskas, 2017;Heede et al, 2020), a forced response to aerosols (Heede & Fedorov, 2021;Kuo et al, 2023), internal variability in the climate system (Olonscheck et al, 2020;Watanabe et al, 2021), missing or poorly simulated teleconnections in climate models (e.g., Y. Dong et al, 2022;Kang et al, 2023;Kim et al, 2022), or a combination of these factors.…”
Section: Discussionmentioning
confidence: 99%
“…While AO-GCMs predicted a warming SST trend in the Central and East Pacific, the region instead experienced a cooling SST trend from 1970 to 2014 (e.g., Coats & Karnauskas, 2017;Seager et al, 2019), which potentially led to the observed megadrought in the SWUS due to a decrease in precipitation (Delworth et al, 2015;Seager & Hoerling, 2014). The cooling of the Central and East Pacific not simulated by AO-GCMs may have been caused by a forced response to greenhouse gas emissions (Coats & Karnauskas, 2017;Heede et al, 2020), a forced response to aerosols (Heede & Fedorov, 2021;Kuo et al, 2023), internal variability in the climate system (Olonscheck et al, 2020;Watanabe et al, 2021), missing or poorly simulated teleconnections in climate models (e.g., Y. Dong et al, 2022;Kang et al, 2023;Kim et al, 2022), or a combination of these factors.…”
Section: Discussionmentioning
confidence: 99%